Bank efficiency in transitional countries: Sensitivity to stochastic frontier design - Zuzana Iršová (Charles University in Prague, Institute of Economic Studies (IES), 2010)
This article provides an empirical insight on the heterogeneity in the estimates of banking efficiency produced by the stochastic frontier approach. Using data from five countries of Central and Eastern Europe, we study the sensitivity of the efficiency score and the efficiency ranking to a change in the design of the frontier. We found that the average scores are significantly smaller when the transcendental logarithmic functional form is used in the profit efficiency measurement and when the scaling effect is neglected in the cost efficiency measurement. The implied bank ranking is robust to changes in the stochastic frontier definition for cost efficiency, but not for profit efficiency.
Keywords: C13; G21; L25; 330; banking; efficiency; stochastic frontier approach; transitional countries; Bank; Kosten; Gewinn; Technische Effizienz; Kosten-Wirksamkeits-Analyse; Osteuropa